Svalbard in the Context of Arctic Security - Andrey A. TODOROV (Arctic and North, 2020)
The article studies Svalbard’s role in the Arctic security agenda, the history of the implementation of the Paris Treaty 1920 with the emphasis on its security provisions, as well as the risks of engaging Svalbard in a military conflict in the region. Despite the demilitarized status of Svalbard, the evaluation of its role in the hard security situation in the Arctic is hampered by several factors. First, Norway sticks to a narrow interpretation of the Treaty 1920 provision that bans any use of the archipelago for warlike purposes. Norway does not consider such actions as the entry of military ships in Svalbard’s ports, overfly of military aircraft, and some other, contradicting with the Russian position, a violation of the Treaty. Second, the development of technologies, particularly of “dual” use, has posed the question of whether the application of some objects situated on Svalbard by the militaries — primarily the stations of space monitoring — are legitimate. Third, as the political uncertainty in the Arctic rises, Svalbard has been more often involved in the worst-case scenarios for the region — as a place vitally important for Russia and simultaneously representing potential vulnerability for NATO. At the same time, the author argues that the threat of a military conflict over Svalbard is minimal. The international Svalbard agenda is dominated by economic issues, whereas the stakeholders stay aware of the significant risks in case of a military conflict on Svalbard.